Anti-platelet therapy does not influence the outcome of patients undergoing hepatic resection for colorectal liver metastases, an observational study. (May 2018) - Boyd-Carson, H.; Irving, G.; Navarro, A.P.; Cameron, I.C.; Gomez, D.S.; ,
Abstract: Aim: To evaluate the impact of anti-platelet therapy on the outcomes of patients undergoing liver resection for CRLM. Secondary aim was to determine whether anti-platelet therapy influenced histo-pathological changes in CRLM. Methods: Patients treated with liver resection for CRLM were identified from a prospectively maintained hepatobiliary database during an 11-year period. Collated data included demographics, primary tumour treatment, surgical data, histopathology analysis and clinical outcome. Results: 454 patients that underwent primary hepatic resections for CRLM were included. 60 patients were on anti-platelet therapy. 241 patients developed recurrent disease and 131 patients have died. Multi-variate analysis identified 4 independent predictors of disease-free survival: tumour number; tumour size; peri-neural invasion; and resection margin. The presence of peri-neural invasion and multiple hepatic metastases were independent predictors of poorer overall survival on multi-variate analysis. Uni-variate analysis showed that the use of anti-platelet therapy was associated with larger tumour size (p=0.031 ) and vascular invasion (p=0.023 ). Conclusion: Anti-platelet therapy does not affect the survival outcome in patients with CRLM following liver resection. Anti-platelet therapy is associated with larger liver metastases and vascular invasion on histo-pathological analysis. Synopsis: A large retrospective study looking at outcomes of patients taking pre operative anti platelet therapy who have undergone liver resection for colorectal liver metastases. Highlights: Antiplatelet therapy in the pre operative period does not improve outcome in patients who have liver resection for colorectal metastases. Perri-neural invasion and multiple hepatic metastases were independent predictors of poor overall survival. Preoperative antiplatelet use is associated with larger tumour and vascular invasion.